Electrolyte additive, electrolyte and high nickel secondary battery
By using electrolytes of phthalic anhydride additives and nitrile additives in high-nickel lithium-ion batteries, the lithium-nickel mixed discharge problem caused by excessive nickel elements is solved, and the battery safety and capacity are taken into account, and the high temperature is improved. Cycling and thermal shock performance.
Patent Information
- Application Number
- CN202411337053.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-25
AI Technical Summary
How to take into account the safety and capacity of high-nickel lithium-ion batteries, especially due to excessive nickel elements, which leads to lithium-nickel mixed discharge, affecting the electrochemical performance and stability of the battery.
An electrolyte containing phthalic anhydride additive and nitrile additive is used to improve interface stability, inhibit cracks and irreversible phase change, and improve the stability of the positive electrode at high voltages.
It effectively improves the safety and capacity of high-nickel lithium-ion batteries, while also improving the high-temperature cycling and thermal shock performance of the battery.
Smart Images

Figure CN118867395B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to electrolyte additives, electrolytes and high-nickel secondary batteries. Background Art
[0002] The positive electrode material of lithium batteries not only affects battery performance, but is also an important factor in determining battery safety. Under the premise of high safety, lithium nickel cobalt manganese oxide, which is a mixture of three transition metals, nickel, cobalt and manganese, in different proportions, is a positive electrode material with higher safety. As the nickel content in the positive electrode material increases, the material's gram capacity increases, but the material's safety decreases. This is because too much nickel may cause dislocation with lithium, resulting in lithium-nickel mixing, making it more difficult for lithium to be deintercalated in the layered structure, resulting in poor electrochemical performance and stability of the battery, affecting the safety of the battery.
[0003] Therefore, how to achieve both safety and capacity of high-nickel lithium-ion batteries is an urgent problem to be solved. Summary of the invention
[0004] In order to solve or partially solve the problems existing in the related art, the present application provides an electrolyte additive, an electrolyte and a high-nickel secondary battery, which can simultaneously improve the safety and capacity of the high-nickel lithium-ion battery.
[0005] In a first aspect, the present application provides an electrolyte additive, comprising a phthalic anhydride additive and a nitrile additive, wherein the phthalic anhydride additive and the nitrile additive satisfy the following relationship with the positive electrode:
[0006]
[0007] Wherein, the mass percentage of the phthalic anhydride additive in the electrolyte is X wt%; the mass percentage of the nitrile additive in the electrolyte is Y wt%; the coating surface density of the positive electrode active material layer of the positive electrode is W g / m 2 ; The mass percentage of nickel element in the positive electrode active material of the positive electrode is A wt%.
[0008] As an optional embodiment, the phthalic anhydride additive and the nitrile additive satisfy the following relationship with the positive electrode:
[0009] .
[0010] As an optional embodiment, 5X-Y>0; and / or, 0.5≤X≤4; and / or, 1≤Y≤6.
[0011] As an optional embodiment, the phthalic anhydride additive is selected from at least one of the following compounds:
[0012]
[0013] Compound 1
[0014]
[0015] Compound 2
[0016]
[0017] Compound 3
[0018] Among them, X1~X4, Y1~Y4, Z1~Z4 are each independently selected from a hydrogen atom, an alkane group of 1 to 5 carbon atoms, an alkene group of 1 to 5 carbon atoms, an alkynyl group of 1 to 5 carbon atoms, a fluorine atom, an aromatic hydrocarbon group, and a cyano group.
[0019] As an optional embodiment, the phthalic anhydride additive is selected from at least one of phthalic anhydride, 4-methylphthalic anhydride, 4-ethynylphthalic anhydride, tetrafluorophthalic anhydride, 3,6-dimethylphthalic anhydride, 3,4,5,6-tetrahydrophthalic anhydride, 3-methyltetrahydrophthalic anhydride, and 1,2,3,6-tetrahydrophthalic anhydride.
[0020] As an optional embodiment, the nitrile additive is selected from glutaronitrile, succinonitrile, adiponitrile, sebaconitrile, azelaic acid dicyanobenzene, terephthalonitrile, pyridine-3,4-dicarbonitrile, 2,5-dicyanopyridine, 2,2,3,3-tetrafluorosuccinonitrile, tetrafluoroterephthalonitrile, 4-tetrahydrothiopyranylmalononitrile, butylene dinitrile, ethylene glycol bis(propionitrile) ether, 1,4,5,6-tetrahydro-5,6-dioxo-2,3-pyrazine dicarbonitrile, 1,3,6-hexane tricarbonitrile, At least one of 1,3,5-cyclohexane trinitrile, 1,3,5-benzene tricyano, 1,2,3-propane tricarbonitrile, glycerol trinitrile, tris(3-cyanopropyl) phosphate, 1,1,3,3-propane tetracarbonitrile, 1,2,2,3-tetracyanopropane, 1,2,4,5-tetracyanobenzene, 2,3,5,6-pyrazine tetracarbonitrile, 3-methyl-3-propyl-cyclopropane-1,1,2,2-tetracarbonitrile, 7,7,8,8-tetracyanoquinodimethane and tetracyanoethylene.
[0021] A second aspect of the present application provides an electrolyte solution, comprising an electrolyte salt, an organic solvent and an additive, wherein the additive comprises the electrolyte solution additive described above.
[0022] The third aspect of the present application provides a high-nickel secondary battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is the electrolyte described above.
[0023] As an optional embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer coated on the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the chemical formula of the positive electrode active material is LiNi a Co b Mn (1-a-b) M c O2, wherein 0.3≤a≤0.9, a+b<1, 0≤c<0.08, and M is at least one of Al, Mg, Zr and Ti.
[0024] As an optional embodiment, the coating surface density of the positive electrode active material layer is W g / m 2 , 90≤W≤200; and / or, the content of nickel element in the positive electrode active material is A wt%, 35≤A≤90.
[0025] The technical solution provided by this application may have the following beneficial effects:
[0026] In this application, the electrolyte includes phthalic anhydride additives and nitrile additives. The carbon-carbon double bonds contained in phthalic anhydride additives can undergo polymerization reactions on the positive and negative electrode surfaces, and the π electrons in the double bonds can couple with the d orbital electrons of the Ni element in the positive electrode active material, thereby improving the interfacial stability of the positive electrode; the acid anhydride contained can form a uniform and stable interfacial film on the positive electrode surface, which can effectively inhibit the generation of cracks and inhibit irreversible phase changes; and the phthalic anhydride additives containing double bonds and acid anhydrides are more significant for improving battery performance than traditional acid anhydrides and additives containing only unsaturated bonds, especially for positive electrode active materials rich in Ni elements. Nitrile additives can effectively complex transition metals at the positive electrode, improve the stability of the positive electrode under high voltage, and thus improve high temperature cycle performance and thermal shock resistance. However, excessive content of nitrile additives will migrate to the negative electrode side, participate in the reduction and destroy the SEI film on the negative electrode side, accelerate the loss of active lithium on the negative electrode side, and thus cause the cycle performance to decay. Phthalic anhydride additives can form films on both the positive and negative electrodes at the same time. The SEI film formed on the negative electrode side has excellent chemical stability and can effectively inhibit the damage of nitrile additives to the negative electrode SEI film. Therefore, the use of phthalic anhydride additives and nitrile additives as additives can improve the stability of the positive and negative electrode interface films, thereby improving the high-temperature cycle performance and thermal shock resistance of the battery.
[0027] The inventor of the present application has found that the performance of the battery is significantly correlated with the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material. Increasing the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material will increase the capacity of the battery, but will deteriorate the high temperature cycle and thermal shock performance of the battery. When the content of phthalic anhydride additives and nitrile additives is too low relative to the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material, the effect of effectively improving the high temperature cycle and thermal shock performance of the battery cannot be achieved. Therefore, the present application can simultaneously improve the capacity and safety of the battery by controlling the relative relationship between the content of phthalic anhydride additives, the content of nitrile additives, the coating surface density of the positive electrode active material layer, and the Ni content in the positive electrode active material. The study found that when the four meet the above relationship, the thermal shock performance and high temperature cycle performance of the battery can be improved while improving the battery capacity.
[0028] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION
[0029] The embodiments of the present application will be described in more detail below. Although the embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0030] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0031] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0032] As the nickel content in the positive electrode material increases, the material's gram capacity increases, but the material's safety decreases. This is because too much nickel may cause dislocation with lithium, resulting in lithium-nickel mixing, making it more difficult for lithium to be deintercalated in the layered structure, resulting in poor electrochemical performance and stability of the battery, affecting the safety of the battery. Therefore, how to achieve both safety and capacity of high-nickel lithium-ion batteries is an urgent problem to be solved.
[0033] In view of the above problems, an embodiment of the present application provides an electrolyte additive that can simultaneously improve the safety and capacity of high-nickel lithium-ion batteries.
[0034] The present application provides an electrolyte additive, including a phthalic anhydride additive and a nitrile additive, and the phthalic anhydride additive and the nitrile additive satisfy the following relationship with the positive electrode:
[0035]
[0036] Wherein, the mass percentage of phthalic anhydride additive in the electrolyte is X wt%; the mass percentage of nitrile additive in the electrolyte is Y wt%; the coating surface density of the positive electrode active material layer of the positive electrode is W g / m 2 ; The content of nickel element in the positive electrode active material of the positive electrode is A wt%.
[0037] In the embodiment of the present application, the positive electrode includes a positive electrode current collector and a positive electrode active material layer coated on the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, a binder and a conductive agent, and the chemical formula of the positive electrode active material is LiNi a Co b Mn (1-a-b) M c O2, wherein 0.3≤a≤0.9, a+b<1, 0≤c<0.08, and M is at least one of Al, Mg, Zr, and Ti. The coating surface density of the positive electrode active material layer refers to the mass of the positive electrode active material coated per unit area when coated on one side, and the content of nickel in the positive electrode active material refers to LiNi x Co y Mn (1-x-y) M z The molar percentage or mass percentage of nickel in O2.
[0038] In the embodiment of the present application, It can be 2.31, 3.08, 4.62, 6.15, 7.69, 8.65, 9.23, 9.89, 10.77, 11.54, 12, 12.31, 13.85, 15.38, 17.31, 18, 19.78, 20, 22.5, 28.57 or any value within the above-defined range, which is not limited in the present application.
[0039] In the embodiment of the present application, the electrolyte comprises phthalic anhydride additives and nitrile additives. The carbon-carbon double bonds contained in the phthalic anhydride additives can undergo polymerization reactions on the positive and negative electrode surfaces, and the π electrons in the double bonds can couple with the d orbital electrons of the Ni element in the positive electrode active material, thereby improving the interfacial stability of the positive electrode; the acid anhydride contained can form a uniform and stable interfacial film on the positive electrode surface, which can effectively inhibit the generation of cracks and inhibit irreversible phase changes; and the phthalic anhydride additives containing double bonds and acid anhydrides are more significant for improving battery performance than traditional acid anhydrides and additives containing only unsaturated bonds, especially for positive electrode active materials rich in Ni elements. Nitrile additives can effectively complex transition metals at the positive electrode, improve the stability of the positive electrode under high voltage, and thus improve high temperature cycle performance and thermal shock resistance. However, excessive content of nitrile additives will migrate to the negative electrode side, participate in the reduction and damage of the negative electrode side SEI film, accelerate the loss of active lithium on the negative electrode side, and thus cause the cycle performance to decay. Phthalic anhydride additives can form films on both the positive and negative electrodes at the same time. The SEI film formed on the negative electrode side has excellent chemical stability and can effectively inhibit the damage of nitrile additives to the negative electrode SEI film. Therefore, the use of phthalic anhydride additives and nitrile additives as additives can improve the stability of the positive and negative electrode interface films, thereby improving the high-temperature cycle performance and thermal shock resistance of the battery.
[0040] The inventor of the present application has found that the performance of the battery is significantly correlated with the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material. Increasing the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material will increase the capacity of the battery, but will deteriorate the high temperature cycle and thermal shock performance of the battery. When the content of phthalic anhydride additives and nitrile additives is too low relative to the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material, the effect of effectively improving the high temperature cycle and thermal shock performance of the battery cannot be achieved. Therefore, the present application can simultaneously improve the capacity and safety of the battery by controlling the relative relationship between the content of phthalic anhydride additives, the content of nitrile additives, the coating surface density of the positive electrode active material layer, and the Ni content in the positive electrode active material. The study found that when the four meet the above relationship, the thermal shock performance and high temperature cycle performance of the battery can be improved while improving the battery capacity.
[0041] As an optional embodiment, the phthalic anhydride additive and the nitrile additive satisfy the following relationship with the positive electrode:
[0042]
[0043] Since when the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material are high, and the content of phthalic anhydride additives and nitrile additives is too low, the high temperature cycle and thermal shock performance of the battery cannot be effectively improved, therefore, appropriately increasing the relative value of the content of phthalic anhydride additives and nitrile additives to the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material can more effectively improve the thermal shock performance and high temperature cycle performance of the battery.
[0044] As an optional embodiment, 5X-Y>0.
[0045] Excessive nitrile additives will migrate to the negative electrode side, participate in the reduction and destroy the SEI film on the negative electrode side, accelerate the loss of active lithium on the negative electrode side, and thus lead to the decay of cycle performance. Phthalic anhydride additives can form films on both the positive and negative electrodes at the same time. The SEI film formed on the negative electrode side has excellent chemical stability and can effectively inhibit the damage of nitrile additives to the negative electrode SEI film. Therefore, controlling the content of phthalic anhydride additives and nitrile additives within a certain relationship can effectively exert the synergistic effect of the two and significantly improve the thermal shock performance and high-temperature cycle performance.
[0046] As an optional embodiment, 0.5≤X≤4.
[0047] When the mass percentage of phthalic anhydride additives in the electrolyte is too low, it cannot achieve a good effect; when the mass percentage of phthalic anhydride additives in the electrolyte is too high, the cycle performance will deteriorate. At this time, due to the excessively high content of additives, the viscosity of the electrolyte will increase, resulting in poor battery rate performance.
[0048] In the embodiment of the present application, the mass percentage X wt% of the phthalic anhydride additive in the electrolyte can be 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or any value within the above-defined range, which is not limited in the present application.
[0049] As an optional embodiment, 1≤Y≤6.
[0050] When the mass percentage of nitrile additives in the electrolyte is too low, they cannot achieve a good effect; when the mass percentage of nitrile additives in the electrolyte is too high, the nitrile additives will migrate to the negative electrode side, participate in the reduction and destroy the SEI film on the negative electrode side, accelerate the loss of active lithium on the negative electrode side, and thus cause the cycle performance to decay.
[0051] In the embodiment of the present application, the mass percentage Y wt% of the nitrile additive in the electrolyte can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt% or any value within the above-defined range, and the present application is not limited to this.
[0052] As an optional embodiment, the phthalic anhydride additive is selected from at least one of the following compounds:
[0053]
[0054] Compound 1
[0055]
[0056] Compound 2
[0057]
[0058] Compound 3
[0059] Among them, X1~X4, Y1~Y4, Z1~Z4 are each independently selected from a hydrogen atom, an alkane group of 1 to 5 carbon atoms, an alkene group of 1 to 5 carbon atoms, an alkynyl group of 1 to 5 carbon atoms, a fluorine atom, an aromatic hydrocarbon group, and a cyano group.
[0060] In the embodiments of the present application, the performance of the phthalic anhydride additive can be changed by selecting different substituents to meet different functional requirements. Among them, the alkynyl group has good polymerization performance, the fluorine atom has a certain wetting effect and strong electronegativity, and is easier to reduce to form a film; the aromatic hydrocarbon group is one of the film-forming components and has good thermal stability; the cyano group can complex the positive electrode transition metal and protect the positive electrode.
[0061] As a preferred embodiment, the phthalic anhydride additive is selected from at least one of phthalic anhydride, 4-methylphthalic anhydride, 4-ethynylphthalic anhydride, tetrafluorophthalic anhydride, 3,6-dimethylphthalic anhydride, 3,4,5,6-tetrahydrophthalic anhydride, 3-methyltetrahydrophthalic anhydride, and 1,2,3,6-tetrahydrophthalic anhydride. The structural formula is as follows:
[0062]
[0063] Phthalic anhydride
[0064]
[0065] 4-Methylphthalic anhydride
[0066]
[0067] 4-Ethynylphthalic anhydride
[0068]
[0069] Tetrafluorophthalic anhydride
[0070]
[0071] 3,6-Dimethylphthalic anhydride
[0072]
[0073] 3,4,5,6-Tetrahydrophthalic anhydride
[0074]
[0075] 3-Methyltetrahydrophthalic anhydride
[0076]
[0077] 1,2,3,6-Tetrahydrophthalic anhydride.
[0078] As an optional embodiment, the nitrile additive is selected from glutaronitrile, succinonitrile, adiponitrile, sebaconitrile, azelaic acid dicyanobenzene, terephthalonitrile, pyridine-3,4-dicarbonitrile, 2,5-dicyanopyridine, 2,2,3,3-tetrafluorosuccinonitrile, tetrafluoroterephthalonitrile, 4-tetrahydrothiopyranide methylmalononitrile, butylene dinitrile, ethylene glycol bis(propionitrile) ether, 1,4,5,6-tetrahydro-5,6-dioxo-2,3-pyrazine dicarbonitrile, 1,3,6-hexane tricarbonitrile, 1 ,3,5-cyclohexane trinitrile, 1,3,5-benzene trinitrile, 1,2,3-propane tricarbonitrile, glycerol trinitrile, tris (3-cyanopropyl) phosphate, 1,1,3,3-propane tetracarbonitrile, 1,2,2,3-tetracyanopropane, 1,2,4,5-tetracyanobenzene, 2,3,5,6-pyrazine tetracarbonitrile, 3-methyl-3-propyl-cyclopropane-1,1,2,2-tetracarbonitrile, 7,7,8,8-tetracyanoquinodimethane and at least one of tetracyanoethylene.
[0079] Corresponding to the aforementioned application function realization method embodiment, the present application also provides an electrolyte, a high-nickel secondary battery and corresponding embodiments.
[0080] The embodiment of the present application also provides an electrolyte solution, comprising an electrolyte salt, an organic solvent and an additive, wherein the additive comprises the aforementioned electrolyte solution additive.
[0081] In an embodiment of the present application, the electrolyte salt includes one or more of lithium hexafluorophosphate LiPF6, lithium difluorooxalatoborate LiODFB, lithium bis(oxalatoborate) LiBOB, lithium difluorobis(oxalatophosphate) LiDFOP, lithium tetrafluoroborate LiBF4, lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI, and lithium difluorophosphate LiPOF2, and the concentration of the electrolyte salt is 0.4 mol / L~2.2 mol / L.
[0082] In an embodiment of the present application, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, methyl acetate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
[0083] The embodiment of the present application also provides a high-nickel secondary battery, including a positive electrode, a negative electrode, a separator and an electrolyte, and the electrolyte is the aforementioned electrolyte.
[0084] As an optional embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer coated on the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the chemical formula of the positive electrode active material is LiNi a Co b Mn (1-a-b) M c O2, wherein 0.3≤a≤0.9, a+b<1, 0≤c<0.08, and M is at least one of Al, Mg, Zr and Ti.
[0085] In the embodiments of the present application, there is no particular restriction on the type of the positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. Preferably, the positive electrode current collector is a metal material.
[0086] In one embodiment, the positive electrode active material layer further includes a conductive agent, a binder and a solvent.
[0087] In one embodiment, the conductive agent includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene.
[0088] In one embodiment, the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.
[0089] In the embodiments of the present application, there is no particular limitation on the material and shape of the diaphragm, as long as the effect of the present application is not significantly impaired.
[0090] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.
[0091] In some embodiments, the battery may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0092] In some embodiments, the outer packaging of the battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.
[0093] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.
[0094] As a preferred embodiment, the coating surface density of the positive electrode active material layer is W g / m 2 , 90≤W≤200.
[0095] Increasing the coating surface density of the positive electrode active material layer is also one of the effective means to increase the battery capacity. However, if the coating surface density of the positive electrode active material layer is too large, it will lead to an increase in the transmission path of the electrolyte, ion transmission will be blocked, and the rate and cycle performance will deteriorate. At the same time, the surface density increases and the active material components increase, which will lead to an increase in side reactions between the active material and the electrolyte. If the coating surface density is too large, the Ni content on the positive electrode sheet will also increase, which will deteriorate the thermal shock performance of the battery. In the embodiment of the present application, the coating surface density of the positive electrode active material layer is W g / m 2 When the limit is 90≤W≤200, the energy density and performance of the battery can be better balanced.
[0096] In the present embodiment, the coating surface density of the positive electrode active material layer is W g / m 2 Can be 90g / m 2 , 100g / m 2 , 150g / m 2 , 180g / m 2 , 200g / m 2 Or any numerical value within the above-defined range, which is not limited in this application.
[0097] As a preferred embodiment, the content of nickel element in the positive electrode active material is A wt%, 35≤A≤90.
[0098] Increasing the Ni content in the positive electrode active material is an effective means to increase the gram capacity of the positive electrode active material, but if the Ni content is too high, the cycle performance and thermal shock performance will deteriorate sharply, and if the content is too low, the effect of increasing the battery capacity cannot be achieved. Therefore, when the content A% of the Ni element in the positive electrode active material is limited to 35%≤A%≤90% in the embodiment of the present application, the energy density and performance of the battery can be better balanced.
[0099] In the embodiments of the present application, the content A% of the Ni element in the positive electrode active material can be 35%, 40%, 50%, 60%, 70%, 80%, 90% or any value within the above-defined range, and the present application is not limited to this.
[0100] In the embodiment of the present application, the negative electrode includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is coated on the surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, a binder and a conductive agent, and the negative electrode active material includes natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy.
[0101] The embodiments of the present application have no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.
[0102] The present application also provides an electrical device, including the above-mentioned high-nickel secondary battery.
[0103] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0104] In order to further understand the present invention, the present application is described below in conjunction with embodiments. These embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0105] The secondary batteries of the embodiments and comparative examples of the present application and their performance tests are prepared and tested according to the method comprising the following steps:
[0106] 1. Preparation of batteries
[0107] 1. Preparation of positive electrode sheet
[0108] The positive electrode active material, the conductive agent acetylene black (Super P) and the polyvinylidene fluoride (PVDF) binder were mixed uniformly at a mass ratio of 97:1.5:1.5, and uniformly dispersed in 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry. The mixed slurry was coated on both sides of the aluminum foil current collector, and then baked, rolled, and cut into pieces to obtain the positive electrode sheet. Among them, the coating surface density of the positive electrode active material layer and the content of Ni element in the positive electrode active material are shown in Tables 1 to 5.
[0109] The content of Ni element in the positive electrode active material can be detected by the following method:
[0110] The positive electrode active material layer on the positive electrode sheet was scraped off, and 5 mg of the positive electrode active material layer was added with 3 mL of concentrated sulfuric acid and 3 mL of concentrated nitric acid in sequence, and heated to 180°C until the solution was clear and transparent. After cooling, water was added to make the volume 50 mL, and the sample was sent for detection. The content of the metal Ni element was tested using an ICP (Inductive Coupled Plasma Emission Spectrometer).
[0111] 2. Preparation of negative electrode sheet
[0112] The negative electrode active material graphite, the conductive agent acetylene black (Super P), the thickener carboxymethyl cellulose CMC and the binder styrene butadiene rubber SBR are mixed evenly in a mass ratio of 94:2:1.2:2.8, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled and cut into pieces to obtain the negative electrode sheet.
[0113] 3. Preparation of electrolyte
[0114] a. Mix ethylene carbonate EC, propylene carbonate PC, dimethyl carbonate DMC and diethyl carbonate DEC in a mass ratio of 10:20:40:30 to form a mixed solvent, remove water with a molecular sieve, set aside, add 1M LiPF6 and mix evenly
[0115] b. Add additives to the colorless transparent liquid obtained in step a (the types and amounts of additives are shown in Tables 1 to 5) to obtain the electrolytes of the embodiments and comparative examples.
[0116] 4. Battery production
[0117] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrode sheets, and the bare cell is obtained by winding and welding the tabs. The bare cell is placed in an aluminum-plastic film for packaging to obtain a battery. The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrodes to play an isolating role, and then wound to a bare cell. The bare cell is placed in an outer packaging bag, dried at high temperature until the water content of the electrode sheet is less than 100ppm, and the electrolyte prepared in each embodiment and comparative example is injected. After vacuum packaging, standing, formation, shaping and other processes, the preparation of the lithium-ion battery of each embodiment and comparative example is completed.
[0118] 2. Battery performance test:
[0119] 1. 45℃ cycle test:
[0120] The test method is: in a 45±2℃ constant temperature box, charge the lithium-ion battery to 4.45V at 1C constant current and constant voltage, cut off the current at 0.05C, and then discharge it to 3V at 1C. Perform multiple charge and discharge cycles under the above conditions, and calculate the capacity retention rate of the battery after 600 cycles, with 5 batteries in each group.
[0121] Capacity retention rate (%) = discharge capacity corresponding to the number of cycles (mAh) / discharge capacity of the third cycle (mAh) * 100%
[0122] The average values of the capacity retention rates of each group of 5 batteries after different cycles are recorded in Tables 1 to 5.
[0123] 2. Thermal shock test:
[0124] The test method is: in a 25±2℃ constant temperature box, charge the lithium-ion battery to 4.45V at 1C constant current and constant voltage, with a cut-off current of 0.05C. Place the battery in an oven, heat the oven at 5℃ / min to 140℃, and keep it for 60 minutes. The battery passes the test if it does not catch fire or explode.
[0125] The pass rates of each group of 20 batteries are recorded in Tables 1 to 5.
[0126]
[0127]
[0128]
[0129]
[0130]
[0131] Note: In Tables 1 to 5, HTCN is 1,3,6-hexanetrinitrile, SN is succinonitrile, ADN is adiponitrile, and PS is propylene sulfite.
[0132] According to the data in Tables 1 to 5, by comparing Examples 1 to 8, it is found that the high temperature cycle performance and thermal shock performance of the battery are improved by using the phthalic anhydride additives provided in the examples of the present application, and the improvement effects are basically the same.
[0133] Comparing Example 1, Examples 9 to 12, and Comparative Example 2, it is found that as the content of phthalic anhydride additives gradually increases, the high temperature cycle performance and thermal shock resistance of the battery are improved accordingly. This is because the carbon-carbon double bonds contained in phthalic anhydride additives can undergo polymerization reactions on the surfaces of the positive and negative electrodes, and at the same time, the π electrons in the double bonds can couple with the d orbital electrons in the transition metal Ni element, thereby improving the interfacial stability of the positive electrode, and the acid anhydride contained can form a uniform and stable interfacial film on the surface of the positive electrode, which can effectively inhibit the generation of cracks and inhibit irreversible phase changes. It is found that phthalic anhydride additives containing both double bonds and acid anhydrides are more significantly improved for battery performance than traditional acid anhydrides and additives containing only unsaturated bonds. Further comparison of Comparative Examples 3 to 5 shows that when the content of phthalic anhydride additives is too low, it cannot achieve a good effect; when the content of phthalic anhydride additives is too high, the cycle performance will deteriorate. At this time, due to the excessively high content of additives, the viscosity of the electrolyte will increase, resulting in poor battery rate performance. When the mass percentage of the phthalic anhydride additive in the electrolyte is X%, and X satisfies 0.5%≤X%≤4%, the cost of the additive and the battery performance can be better balanced.
[0134] Comparing Example 11, Examples 13 to 17, and Comparative Example 6, it is found that as the content of nitrile additives gradually increases, the high temperature cycle performance and thermal shock performance of the battery are improved. This is because nitrile additives can participate in the positive electrode film formation, can effectively complex the transition metal of the positive electrode, and improve the stability of the positive electrode active material under high voltage and high temperature. Further comparison of Comparative Examples 7 to 9 found that when the content of nitrile additives is too low, it cannot achieve a good effect; when the content of nitrile additives is too high, the cycle performance will deteriorate. At this time, due to the excessive content of additives, the viscosity of the electrolyte will increase, resulting in poor battery rate performance. When the mass percentage of nitrile additives in the electrolyte is Y%, and Y satisfies 1% ≤ Y% ≤ 6%, the additive cost and battery performance can be better balanced. Further comparison of Comparative Examples 19 and 20 found that when the content of nitrile additives is too high compared to the content of phthalic anhydride additives, the nitrile additives will migrate to the negative electrode side, participate in the reduction and destroy the SEI film on the negative electrode side, accelerate the loss of active lithium on the negative electrode side, and thus cause the cycle performance to decay. Phthalic anhydride additives can form films on both the positive and negative electrodes at the same time. The SEI film formed on the negative electrode side has excellent chemical stability and can effectively inhibit the damage of nitrile additives to the negative electrode SEI film. Therefore, when the content of phthalic anhydride additives and nitrile additives is controlled at a certain level and 5X-Y>0 is satisfied, the synergistic effect of the two can be effectively exerted, significantly improving the thermal shock performance and high temperature cycle performance.
[0135] Comparing Examples 1 to 8, as well as Comparative Examples 1 and 10 to 14, it is found that only when phthalic anhydride additives and nitrile additives are present at the same time can the thermal shock and high-temperature cycle performance of the battery be significantly improved. Phthalic anhydride additives have both cyclic unsaturated functional groups and acid anhydride functional groups, and can form films on the positive and negative electrodes at the same time. Compared with simple benzene, acid anhydride, acid anhydride without unsaturated bonds such as hexahydroanhydride, and cyclic unsaturated additives, the improvement effect is more obvious, and only phthalic anhydride additives can play a good synergistic role with nitrile additives. And when the nitrile additive is other positive electrode film-forming additives such as PS and isocyanate, it is impossible to effectively form a good synergistic effect with phthalic anhydride additives.
[0136] Comparing Example 16 and Examples 18 to 22, it is found that as the coating surface density of the positive electrode active material layer increases, the cycle performance and thermal shock performance of the battery first increase and then decrease. This is because the coating surface density of the positive electrode active material layer is too large, which causes the transmission of the electrolyte to be blocked, and the rate and cycle performance will deteriorate. At the same time, if the coating surface density of the positive electrode active material layer is too large, the active material component will also increase, resulting in an increase in the side reactions between the active material and the electrolyte. At the same time, the absolute Ni element content on the positive electrode sheet will also increase, which will deteriorate the thermal shock performance of the battery. Further comparison of Comparative Examples 15 and 16 found that when the coating surface density of the positive electrode active material layer is W g / m 2 , and when W satisfies 90≤W≤200, the energy density and performance of the battery can be better balanced.
[0137] Comparing Example 16 and Examples 23 to 28, it is found that as the content of Ni in the positive electrode active material increases, the cycle performance and thermal shock performance of the battery first increase and then decrease. This is because too much nickel will cause lithium-nickel mixing due to dislocation with lithium. The greater the nickel ion concentration, the more difficult it is to deintercalate lithium in the layered structure, resulting in poor electrochemical performance. The higher the Ni content, the more serious the lithium-nickel mixing and the higher the surface residual alkali. Therefore, the higher the Ni content, the worse the thermal stability of the material (safety, cycle stability, storage, etc.). Further comparison of Comparative Examples 17 and 18 shows that when the content of Ni in the positive electrode active material is A%, and A satisfies 35%≤A%≤90%, the energy density and performance of the battery can be better balanced.
[0138] Comparison of Example 1, Examples 9 to 30, and Comparative Examples 21 to 25 revealed that the performance of the battery is significantly correlated with the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material. Increasing the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material will increase the capacity of the battery, but will deteriorate the high temperature cycle and thermal shock performance of the battery. When the content of phthalic anhydride additives and nitrile additives is too low relative to the coating surface density of the positive electrode active material layer and the Ni content in the positive electrode active material, the effect of effectively improving the high temperature cycle and thermal shock performance of the battery cannot be achieved. And:
[0139] When satisfied When the battery capacity is increased, the thermal shock resistance and high temperature cycle performance of the battery can be improved. Further comparison of Examples 12 to 30 shows that when When the temperature is high, the battery's high temperature cycle and thermal shock performance are better.
[0140] Although the present application has been described with reference to preferred embodiments, it will be appreciated by those skilled in the art that various changes may be made and equivalents may be substituted for its elements without departing from the scope of the present application. In addition, many modifications may be made to adapt specific situations or materials to the teachings of the present application without departing from the substantive scope of the present application. Therefore, the present application is not intended to be limited to the specific embodiments disclosed as the best mode of implementing the present application contemplated, but the present application will include all embodiments falling within the scope of the appended claims.
[0141] All ranges disclosed in this application are inclusive of the endpoints, and the endpoints are combinable with each other.
[0142] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. An electrolyte additive, characterized in that: The invention comprises a phthalic anhydride additive and a nitrile additive, and the phthalic anhydride additive and the nitrile additive satisfy the following relationship with the positive electrode: Wherein, the mass percentage of the phthalic anhydride additive in the electrolyte is X wt%; the mass percentage of the nitrile additive in the electrolyte is Y wt%; the coating surface density of the positive electrode active material layer of the positive electrode is W g / m 2 ; The mass percentage of nickel element in the positive electrode active material of the positive electrode is A wt%; 0.5≤X≤4, 1≤Y≤6, 90≤W≤200, 35≤A≤90, 5X-Y>0, and the chemical formula of the positive electrode active material is LiNi a Co b Mn (1-a-b) M c O2, wherein 0.3≤a≤0.9, a+b<1, 0≤c<0.08, and M is at least one of Al, Mg, Zr and Ti; and the phthalic anhydride additive is selected from at least one of phthalic anhydride, 4-methylphthalic anhydride, 4-ethynylphthalic anhydride, tetrafluorophthalic anhydride, 3,6-dimethylphthalic anhydride, 3,4,5,6-tetrahydrophthalic anhydride, 3-methyltetrahydrophthalic anhydride and 1,2,3,6-tetrahydrophthalic anhydride.
2. The electrolyte additive according to claim 1, characterized in that: The nitrile additive is selected from glutaronitrile, succinonitrile, adiponitrile, sebaconitrile, azelaic acid dicyanobenzene, terephthalonitrile, pyridine-3,4-dicarbonitrile, 2,5-dicyanopyridine, 2,2,3,3-tetrafluorosuccinonitrile, tetrafluoroterephthalonitrile, 4-tetrahydrothiopyranide methylmalononitrile, butylene dinitrile, ethylene glycol bis(propionitrile) ether, 1,4,5,6-tetrahydro-5,6-dioxy-2,3-pyrazine dicarbonitrile, 1,3,6-hexane tricarbonitrile, 1,3,5- At least one of cyclohexane trinitrile, 1,3,5-benzene tricyano, 1,2,3-propane tricarbonitrile, glycerol trinitrile, tris(3-cyanopropyl) phosphate, 1,1,3,3-propane tetracarbonitrile, 1,2,2,3-tetracyanopropane, 1,2,4,5-tetracyanobenzene, 2,3,5,6-pyrazine tetracarbonitrile, 3-methyl-3-propyl-cyclopropane-1,1,2,2-tetracarbonitrile, 7,7,8,8-tetracyanoquinodimethane and tetracyanoethylene.
3. An electrolyte, characterized in that: The invention comprises an electrolyte salt, an organic solvent and an additive, wherein the additive comprises the electrolyte additive according to any one of claims 1 to 2.
4. A high nickel secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is the electrolyte according to claim 3.
5. The high nickel secondary battery according to claim 4, characterized in that: The positive electrode includes a positive electrode collector and a positive electrode active material layer coated on the positive electrode collector, wherein the positive electrode active material layer includes a positive electrode active material.
Citation Information
Patent Citations
Electrolyte and lithium-ion battery applying electrolyte
CN110148784A
Electrolyte and preparation method thereof and lithium ion battery
CN110649318A
Lithium ion battery
WO2024109446A1